Sesmic Retrofitting of Bridges: Mitigating the Risk of Earthquake Damage (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The immediate effect of the earthquake is dislocation,breakage and destruction of transport and communication facilities.Bridge act as the vital connectivity element inroad networking. Bridges are also considered to be structures of post-earthquake importance because of the indeed for emergency response, relief and rehabilitation measures. It is known from experience that bridges are vulnerable to earthquake damage.Thus the safety and protection of bridges in earthquakes it is most important.There are number of bridges which are designed according tool codes when modern seismic provisions were not developed. Such bridges are mostly found deficient and may need seismic retrofitting. Seismic retrofitting of existing bridge sis one method of mitigating the risk that currently exists.